Determination of normal reference values of biochemical, hematological, and hormonal changes during pregnancy - Fateme Tashrifi; Seyed Javad Hosseini; Bagher Moradi (Mashhad University of Medical Sciences, 2018)
Introduction: Reference laboratory values undergo major changes during pregnancy and if they were defined according to non-pregnant women laboratory reference values, can lead to inappropriate decisions and have adverse effects on pregnancy. Because of the physiological changes in the body of pregnant women, the reference values are not standardized in the medical diagnostic labs. Therefore, the present study was conducted to determine the reference values of biochemical, hematological and hormonal tests during pregnancy. Methods: In the present study, the articles were extracted from SID, Google Scholar, ISI, MedLib, and PubMed databases. Our research was performed without any time or language limitation. Results: In our study, 46 diagnostic laboratory values differentiated in pregnant women were extracted from 21 reports. These changes were found in complete blood count, coagulation proteins, alkaline phosphatase, albumin, urea-creatinine, and hormones, such as aldosterone, cortisol, estradiol, progesterone, testosterone prolactin, and human chorionic gonadotropin. Conclusion: Examination of laboratory values in pregnant woman showed that there were significant differences in the laboratory values between the pregnant and non-pregnant women. So the recognition of these differences could be useful in the prevention of making incorrect decisions by physicians and pregnant women.